Characterization and classification of anaerobic ammonium oxidation (anammox) bacteria - ZHENG Ping; ZHANG Lei (浙江大学学报. 农业与生命科学版)
Anaerobic ammonium oxidation (anammox) is one of important discoveries in both environmental and microbiological fields. It supplements biogeochemistry of nitrogen cycle in nature, extends microbial diversity and urges development of novel nitrogen removal biotechnology. Recently, plenty breakthroughs have been made in the research of anammox bacteria. Their properties in bacterial morphology, cytochemistry, enrichment and isolation, physiology and biochemistry, ecology were revealed, and probable metabolic models were proposed, and the important enzymes were purified and characterized. A family of Anammoxaceae including five genus, nine species has been established. This paper is a systematic review in the features of anammox bacteria and the nine identified species.